The three faces of factor intensities - Hamid Beladi; Ronald Winthrop Jones; Sugata Marjit (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1995)
The concept of factor intensity has played a key role in the development of international trade theory. The factor proportions utilized in the production of commodities differ from activity to activity. Some commodities employ a higher ratio of capital to labor than do others, and the basic Heckscher-Ohlin Theorem explaining the pattern of international trade links a nations's factor endowment proportions of capital to labor to the capital/labor factor intensities of its export activities. This theorem has been exhaustively analyzed to reveal that exceptions may occur when technologies exhibit factor-intensity reversals, when demand conditions are highly asymmetric between countries, or when the number of factors and commodities exceeds the frequently-assumed value two. Our remarks in this paper proceed along different lines. We argue that in explaining the link between factor intensities associated with a nation's exports, imports or non-traded activities and that nation's factor endowment base, at least three rather separate roles for factor intensities can be identified. Once this is done, paradoxical statements such as, "Exports from laborabundant countries are capital intensive", can be shown to have some validity. Furthermore, in explaining this position recourse is had to various characteristics of technology and trade which have been in the forefront of recent developments in trade theory, e.g., quality differences in an intra-industry setting, increasing returns to scale activities, uncertainty in production, and the role of services in trade.
Keywords: 330; Außenwirtschaftstheorie; Faktorintensität; Theorie